PEMBENTUKAN VERBA BERWAZAN فعّل /FA’'ALA/ DALAM KAMUS AL-MUNAWWIR CETAKAN KE-14 TAHUN 1997 - Zainul Arifin, Tri Yanti Nurul Hidayati (Arabic Literature Department, 2015)
The research discuss about the formation of the verb stem فعّل /fa''ala/ in alphabet /hamzah/ (أ) /wau/ (و) and /ya>‘/ (ي) and about the posed meaning of the verb stem فعّل /fa''ala/ in alphabet /hamzah/ (أ) /wau/ (و) and /ya>‘/ (ي). The purposes in this research are describe the process of formation of the verb stem فعّل /fa''ala/ in alphabet /hamzah/ (أ) /wau/ (و) and /ya>‘/ (ي) and describe the meaning arising from the verb stem فعّل /fa''ala/ in alphabet /hamzah/ (أ) /wau/ (و) and /ya>‘/ (ي).The research applied qualitative descriptive research method including three stages, data collection, data analysis, and presentation of the results. Tapping technique, observation technique, and note technique as a method of providing data. Direct segmenting constituents technique and deletion technique as the method of data analysis, and informal techniques as the method of presenting the results of the data analysis. This results showed that the formation of verbs stem /fa''ala/ always through the process of idhgam or the process of inserting two letters are same into a single letter shadda. In addition it same letters in the middle of words or of species /'ain fi'l/, instead of one of the letters in the word (سألتمونيها). There are a variety stem of the verb before stem/fa''ala/ which determines the capacity of verbs that can be stem /fa''ala/. The formation of verbs stem /fa''ala/ are means /litta'diyah/ or to shows the transitive of verb, /littaktsīr/ shows the meaning of reply, /ar-Raddu bi ma’nā fi’l al-Mujarrad/ shows the meaning as a the meaning original verb, and /liddalālah 'alā al-Masyīila al-Maudhli' or littaujīh/ shows the meaning go to the somewhere. while the dominant is means /litta'diyah/.